Theoretical Justification and Calculation of the Integral Indicator Related to Innovative Activity of an Organization - Vasilieva, Ekaterina; Vasiliev, Evgeniy; Danilova, Elena (International Journal of Engineering and Technology, 2018)
The current economic and political situation poses challenges for the further development of the Russian economy. Problems of the discrepancy between the existing economic, administrative, regulatory framework and the tasks set were identified during the implementation of the National Technological Initiative 2035. Problem of compatibility of social organization and ability of social systems to change is becoming urgent. To efficiently overcome the identified difficulties, it is necessary to develop the existing theories of organizational development (hereinafter â€“ OD), the organization’s innovative activity being an important component of many of them. Formation of empirical data is required for the formation of strategic plans within the framework of OD theories. The adapted author’s system of innovative indicators was used to solve this problem in the study. Innovative activity of any organization can be viewed as a sequential cyclic passage of stages that generally describe the life cycle of any innovative product, from the moment of inception to achieving specific economic results while implementing the final innovative solution. A promising rating method is proposed as part of the adapted system to determine the share of innovatively active personnel in enterprises. This method can be successfully applied in an enterprise of any size and any branch of the economy. It is suggested to use well-established economic methods (dynamic approach, efficiency approach, dynamic efficiency approach), which allows to control and subsequently correct any aspects of the enterprise activity related to innovation at various stages of implementation of innovative ideas (projects). As a result, using an integrated assessment of the innovative activity of the enterprise as a source of empirical data to determine the dynamics of development of organizations in the population under consideration, as well as the main provisions of the population selection model of OD allows to identify organizations that produce "perfect change patterns" and model innovative and OD processes applied to a specific organization, given the forecasting of the results of the changes implemented in the market sector. Â